Correction: Antibody-coated microstructures for selective isolation of immune cells in blood. Issue 4 (3rd February 2022) - Li, Jiyu; Liu, Ya; Ren, Jifeng; Tay, Benjamin Zikai; Luo, Tao; Fan, Lei; Sun, Dong; Luo, Guannan; Lau, Denvid; Marcos,; Lam, Raymond H. W.
Abstract : Correction for 'Antibody-coated microstructures for selective isolation of immune cells in blood' by Jiyu Li et al., Lab Chip, 2020, 20, 1072–1082, DOI: ; 10.1039/D0LC00078G .